Stage of maturity and its effect on seed qualities in pigeonpea cultivars - SHIVAGOUDA PATIL; RAJENDRA PRASAD S.; THIRUMALARAJU G.T.; SIDDARAJU R. (Seed Research, 2026)
Field experiment was carried out at National Seed Project, University of Agricultural Sciences Bangalore during kharif 2010 to determine the optimum stage of harvest for getting higher quality seeds in pigeonpea (Cajanus cajan (L.) Mill sp.) cultivars BRG-1 and BRG-2. The pods of both cultivars were harvested at 45, 50, 55 and 60 days after anthesis (DAA). Our results showed that, the cultivars BRG-1 and BRG-2 attained physiological maturity at 55 and 50 DAA respectively and at this stage the seeds recorded higher dry matter accumulation (12.26 g/10pods and 6.33 g/10pods) with maximum germination (80.50% & 83.25%), vigour index -1 (2380 & 2800) and vigour index-II (3100 & 3368), field emergence (78.25% & 79.25%), pH of seed leachate (6.35 & 6.31), total dehydrogenase activity (2.50 & 1.76), and lowest electrical conductivity (1.52 mS & 1.22 mS), minimum seed infestation (18.00% & 11.75%) respectively. The findings of the study conclude that, pigeonpea cultivars BRG-1 and BRG-2 could be harvest at 55 and 50 DAA for better seed quality.